The Effect of Ethanol Extract of Guava (Psidium guajava L) Leaf on Hypercholesterolemia-Diabetic White Rats Male Induced by High Fat Feed and Streptozotocin - Tandi, Joni; Diana Pratiwi, Franciska; surisna, surisna; Puspita Dewi, Niluh; Magfirah, Magfirah (Universitas Tadulako, 2021)
This study aims to determine the effect of guava (Psidiium guajava L) leaf extract on hypercholesterolemia-diabetic white rats male and the effective dose for reducing cholesterol and blood glucose levels. This study is a laboratory experimental study using 30 rats divided into 6 test animals. the treatment group, each group consisted of 5 rats. Group I was normal control, group II negative control was given Na-CMC suspension, group III as positive control was given simvastatin group IV dose 150 mg / kg BW, group V dose 250 mg / kg BW and group VI dose 350 mg / kg BW. The results showed that the ethanol extract of guava leaves influenced reducing blood glucose levels of male white rats with an effective dose of 250mg / kg BW with an average reduction of 119 mg/dL and effective reducing the cholesterol levels at a dose of 150 mg /kg BW with an average reduction of 28,33 mg/dL.